Pieces of her : a novel - Slaughter, Karin, 1971- (New York : William Morrow, an imprint of HarperCollinsPublishers, 2018)
"Andrea knows everything about her mother, Laura. She knows she$1 (Bs spent her whole life in the small beachside town of Belle Isle; she knows she$1 (Bs never wanted anything more than to live a quiet life as a pillar of the community; she knows she$1 (Bs never kept a secret in her life. Because we all know our mothers, don$1 (Bt we? But all that changes when a trip to the mall explodes into violence and Andrea suddenly sees a completely different side to Laura. Because it turns out that before Laura was Laura, she was someone completely different. For nearly thirty years she$1 (Bs been hiding from her previous identity, lying low in the hope that no one would ever find her. But now she$1 (Bs been exposed, and nothing will ever be the same again. The police want answers and Laura$1 (Bs innocence is on the line, but she won$1 (Bt speak to anyone, including her own daughter. Andrea is on a desperate journey following the breadcrumb trail of her mother$1 (Bs past. And if she can$1 (Bt uncover the secrets hidden there, there may be no future for either one of them."--s
Keywords: Mothers and daughters -- Fiction; Violence -- Fiction; Identity (Psychology) -- Fiction; Family secrets -- Fiction; Detective and mystery fiction; Thrillers (Fiction)